Pcr Amplification of Ornithine Decarboxylase (ODC) Gene Fragment from Tobacco (Nicotiana tabacum L.) cv. Temanggung - Ira Djajanegara; Sabar Pambudi; Retno Lestari; Nina Artanti (Research Center for Biotechnology - Indonesian Institute of Sciences (LIPI), 2004)
In order Lo create an antisense construct of the gene encoding Ornithine Decarboxylase (ODC) from tobacco (Nicotiana tabacum L.) cv. Temanggung, the target gene must be isolated. In this paper. we present the PCR amplification of a fragment from putative gene encoding ODC from tobacco cv. Temanggung. Leaf genomic DNA was i olated and used as the template for PCR. PCR optimization was done by adjusting the annealing temperature and the cycle number. Verification of the fragment obtained was also done using the second primer pairs .